Cold-Adapted Fungi: Goldmine of Biomolecules Applicable in Industry - Iga Jodłowska; Aneta Monika Białkowska (Applied Sciences)
Fungi, which are widely distributed across the Earth, have successfully managed to colonize cold environments (e.g., polar regions, alpine ecosystems, and glaciers) despite the challenging conditions for life. They are capable of living in extremely harsh environments due to their ecological versatility and morphological plasticity. It is also believed that lower eukaryotes are the most adapted to life at low temperatures among microorganisms that thrive in cold environments. They play important ecological roles, contributing to nutrient recycling and organic matter mineralization. These highly specialized microorganisms have developed adaptation strategies to overcome the direct and indirect harmful influences of low temperatures. They have evolved a wide range of complex and cooperative adaptations at various cellular levels, including modifications to the cell envelope and enzymes, the production of cryoprotectants and chaperones, and the development of new metabolic functions. Adaptation to cold environments has made fungi an exciting source for the discovery of new cold-adapted enzymes (e.g., proteinases, lipases) and secondary metabolites (e.g., pigments, osmolytes, polyunsaturated fatty acids) for widespread use in biotechnology, food technology, agriculture, pharmaceutics, molecular biology, textile industry, and environmental bioremediation in cold climates. This review aims to provide a comprehensive overview of the adaptive strategies employed by psychrophilic yeasts and fungi, highlighting their ecological roles and biotechnological potential. Understanding these adaptive mechanisms not only sheds light on microbial life in extreme environments but also paves the way for innovative applications in the food industry and agriculture.